Rancang Bangun Lab Komputer Virtual Berbasis Cloud Computing Menggunakan Ovirt pada Jaringan Terpusat - Sumarto Sumarto; Ahmad Hamim Thohari; Meyti Eka Apriyani (JURNAL INTEGRASI, 2014)
Students at vocational colleges such as Batam State Polytechnic has a lab course load greater than theory, this makes the need for lab use over existing lab sessions. Although they has owned notebook, diversity of operating system and cost for software that used in practicum became problem. Virtual computer lab discourse as a solution of the problem. After testing with Proxmox platform, known performance and recommendation to the needs of a virtual computer lab. In addition it is recommended to test with other virtualization platforms. This study attempted to do a virtual computer lab design based cloud computing platform using Ovirt on a centralized network. The test results of a virtual computer lab with object-based programming case study shows, the server used during the test can run a virtual computer lab with 10 computers well. So, to meet the needs its necessary to use 2 servers as Ovirt Engine and Ovirt Node with high specification especially for hard disk, RAM and processor.